Islamic Virtues in The Javanese Muslim Tradition: A Philosophical Investigation on Damardjati Supadjarâ€™s Religious Ethics - M. Nur Prabowo Setyabudi (Ijtimā`iyya: Journal of Muslim Society Research, 2016)
Since firstly transmitted in Java and became a major religion, about 700 years agoor even more, Islam has met with many older cultures and traditions that had been existed hundreds of years before, and grew so far with numerous model of synthesises. Universal values of Islam met with local genius. The universal messages of Islam, interacting with diverse etnicity and particularvalue, had created some new sytheses. The universal value did not pass away. Vice versa, it constantly adhereable and penetrated into the traditional way of life. Indeed, Islam manifested and transformed to be a new colour one: being localized in a new society. The new entity, on eventually, addopted by their socialite in particular, and their member of community in general. This is the fact that we can say to the javanesemoslem community, and will be discussed in the article. It is islamic virtues in the new tradition. The present article, however, will focuse on the religious ethics and the certain figure in the community, DamardjatiSupadjar, and give more specific attention through his concept of individuality (self) and sociality, notably â€œself-recognitionâ€. The contain is results of bibliographic research. The main method of this article is philosophical interpretation and description.